Study on Rumen Degradability and Intestinal Digestibility of Mutton Sheep Diets with Different Concentrate-to-Forage Ratios and Nonfiber Carbohydrates/Neutral Detergent Fiber Ratios - Xunyu Guo; Lei Sun; Zibin Zheng; Xiaogao Diao; Liwen He; Xiaoling Dong; Wei Zhang (Animals)
This study was conducted to investigate the rumen degradability and intestinal digestibility of mutton sheep diets different in concentrate-to-forage ratio, NFC/NDF, and ingredient combination, providing a guideline for the selection of a fattening diet for mutton sheep. Twenty-eight diets composed of four raw material combinations and seven concentrate-to-forage ratios and four three-year-old mutton sheep with permanent rumen fistulas were used in the experiments. The nutrient composition of the diets was first analyzed, and then an in situ method and in vitro three-step method were separately used to measure the rumen degradability and intestinal digestibility, mainly focusing on the effects of dietary concentrate-to-forage ratio and NFC/NDF as well as the effects of soybean meal and soybean meal replacement and peanut vine and peanut vine replacement. The results showed that a dietary concentrate-to-forage ratio of 70:30~80:20 and an NFC/NDF ratio of 1.5~2.0 are recommended for fattening mutton sheep, and low-cost cottonseed meal and rapeseed meal can be feasible alternative protein sources to soybean meal. In addition, the nutritional values of sunflower seed hulls and rice hulls for mutton sheep are lower than that of peanut vine. Such a study can provide practical guidelines for enterprises and farmers, being of important significance for the high-quality development of the mutton sheep industry.